AL MAQASHID AL SYAR’IYYAH SEBAGAI BAGIAN DARI AL QAWA’ID AL USHULIYYAH AL TASYRI’IYYAH - Nasril Albab Mochamad (JURNAL INDO-ISLAMIKA, 2018)
The basic thought of maqashid has existed since the time of the companions, even when the Prophet was still living with them. If it is said that maqashid and maslahah are closely related, then it can be said that the forerunner of thoughts related to the concept of maqashid also departed from the thought of the argument of syara 'and its use as maslahat becomes an important consideration as a legal argument when there is no sharih text from the Qur'an or hadith and ordered to perform ijtihad. It is in this ijtihad process that a mujtahid bases his thoughts on the consideration of goodness during the stipulation of the law. If there is maslahat, there is the law of Allah SWT and vice versa, if there is madharat, then the prohibition will be taken by a mujtahid. Caliph Umar ra's policy based on a maqashid approach was not less than forty issues, all of which could be classified into several groups; regarding property (amwal), had and punishments and consequences (hudud wa 'uqubat), marriage and divorce (zawaj wa thalaq), inheritance (mirats) and other problems.